The Effect of Religion on Psychological Resilience in Healthcare Workers During the Coronavirus Disease 2019 Pandemic - Chang, Mei-Chung; Chen, Po-Fei; Lee, Ting-Hsuan; Lin, Chao-Chin; Chiang, Kwo-Tsao; Tsai, Ming-Fen; Kuo, Hui-Fang; Lung, For-Wey (Frontiers in Psychology, 2021)
Background: Healthcare workers in the front line of diagnosis, treatment and care of patients with coronavirus disease 2019 (COVID-19) are at great risk of both infection and developing mental health symptoms. This study aimed to investigate: 1) whether healthcare workers in general hospitals experience higher mental distress than those in psychiatric hospitals; 2) the role played by religion and alexithymic trait in influencing the mental health condition and perceived level of happiness of healthcare workers amidst the stress of the COVID-19 pandemic; and 3) factors that influence the resilience of healthcare workers at 6-weeks’ follow-up. Methods: Four-hundred and fifty-eight healthcare workers were recruited from general and psychiatric hospitals, and 419 were followed up after 6 weeks. All participants filled out the 20-item Toronto Alexithymia Scale, five-item Brief-Symptom Rating Scale, and the Chinese Oxford Happiness Questionnaire. Results: Under the stress of the COVID-19 pandemic, 12.3% of frontline healthcare workers in general hospitals reported having mental distress and perceived lower social adaptation status compared with those working in psychiatric hospitals. Christians/Catholics perceived better psychological well-being, and Buddhists/Taoists were less likely to experience mental distress. The results at 6 weeks of follow-up showed that the perceived lower social adaptation status of general hospital healthcare workers was temporary and improved with time. Christian/Catholic religion and time had independent positive effects on psychological well-being, however the interaction of Christian/Catholic religion and time had a negative effect. Conclusions: Collectivism and individualism in the cultural context are discussed with regards to alexthymic trait and Buddhist/Taoist and Christian/Catholics religious faiths. Early identification of mental distress and interventions should be implemented to ensure a healthy and robust clinical workforce for the treatment and control of the COVID-19 pandemic.